PEMETAAN TINGKAT BERPIKIR KREATIF MAHASISWA PENDIDIKAN MATEMATIKA DALAM PEMECAHAN MASALAH SOAL ANALISIS REAL 2 DITINJAU DARI GAYA BELAJAR - Hidayatulloh, Hidayatulloh (JURNAL E-DUMATH, 2015)
AbstractÂ The research aims to assess how high the level of education of students creative thinking in problem solving mathematical problems of Real Analysis 2 in terms of learning styles visual, auditory and tactual. This research is a quantitative descriptive. The samples of the research were taken by using the stratified random sampling technique. Data were analyzed based on three indicators to assess the ability of creative thinking of learners in fluency, flexibility and innovation. Results of the study describes how high the level of creative thinking to each students learning style in solving problems of Real Analysis 2. The conclusion shows that the visual learners "very creative (level 4)",auditory learners"creative enough (level 2)",and tactual learners "creative (level 3)" in solving problems in the Real Analysis 2 STKIP MuhammadiyahPringsewu Lampung Â Keywords : Creative Thinking, Problem Solving, Learning Style